Social Media Use and its Impact on Women: A Study of Haryana - Dave, Vandana (Pancasila International Journal of Applied Social Science, 2025)
Social networking sites provide a platform for sharing knowledge and information on issues of interest with wider audience.  It facilitates interpersonal connection, community building, activism and development of diverse perspectives. Despite numerous beneficial aspects of social media platform, it may negatively affect women’s participation and cause psychological harm to women. The impact of social media cannot be understand in isolation with social and cultural contexts and to facilitate an in depth understanding of its impact broader power structure that govern contemporary gender relations needs to be understand. The study aims to find out the pattern of use of social media platforms by rural and urban girls and women, assess the impact of use of social media on their daily life, family relationship, on mental and emotional health and analyse the victimisation of girls through social media, if any. It is survey type research and data was collected with the help of a self structured questionnaire. Random sampling technique was applied to select sample units and 200 women and girls, rural and urban both filled the questionnaire. Findings show that for majority of respondents both rural and urban, whatsapp is the most frequently used social media platform followed by YouTube. It facilitates new learning and helps in maintaining interpersonal relationship, however, many of the respondents show agreement with the negative influences of social media. They believe that it promotes unethical material deteriorating social norms, promoting gender stereotypes affecting gender relationship and creating confusion.